Medication Adherence and Healthcare Costs in Chronically Ill Patients Using German Claims Data - Johannes Wendl; Andreas Simon; Martin Kistler; Jana Hapfelmeier; Antonius Schneider; Alexander Hapfelmeier (Applied Health Economics and Health Policy, 2023)
Background and Objective: Despite the importance of medication adherence for chronically ill patients and the vast literature on its relationship to costs, this field suffers from methodological limitations. These are caused, amongst others, by the lack of generalizability of data sources, varying definitions of adherence, costs, and model specification. We aim to address this with different modeling approaches and to contribute evidence on the research question. Methods We extracted large cohorts of nine chronic diseases ( n = 6747–402,898) from German claims data of stationary health insurances between 2012 and 2015 (t0–t3). Defined as the proportion of days covered by medication, we examined the relationship of adherence using several multiple regression models at baseline year t0 with annual total healthcare costs and four sub-categories. Models with concurrent, and differently time-lagged measurements of adherence and costs were compared. Exploratively, we applied non-linear models. Results Overall, we found a positive association between the proportion of days covered by medication and total costs, a weak association with outpatient costs, positive with pharmacy costs, and frequently negative with inpatient costs. There were major differences by disease and its severity but little between years, provided adherence and costs were not measured concurrently. The fit of linear models was mainly not inferior to that of non-linear models. Conclusions The estimated effect on total costs differed from most other studies, which highlights concerns about generalizability, although effect estimates in sub-categories were as expected. Comparison of time lags indicates the importance of avoiding concurrent measurement. A non-linear relationship should be considered. These methodological approaches are valuable in future research on adherence and its consequences.
Keywords: 610; Pharmacoeconomics and Health Outcomes; Quality of Life Research; Health Economics; Health Administration; Public Health